Political Competition: How to Measure Party Strategy in Direct Voter Communication using Social Media Data? - Silke Sturm (University of Hamburg, Chair of International Economics, 2019)
Political competition, party strategy and communication in the era of social media are growing issues. Due to the increasing social media presence of parties and voters alike, direct communication is more important for party competition. This paper aims to improve the methodological approach used to analyze political competition and communication. The dataset includes over 30,000 Facebook status messages posted by seven German parties from January 2014 until February 2018. Topic modeling, which is commonly used in other fields, allows for evaluating party communication on a daily basis. The results show the high accuracy of calculating party-relevant issues. To determine the tone of the debate, a sentiment analysis was conducted. The prevalence of topics and sentiments over time allows for precise monitoring of the political debate.
Keywords: C81; D72; D83; D91; 330; Political competition; Party strategy; Decision making; Social media; Topic models; Sentiment analysis